Revealing the role of renewable energy consumption and digitalization in energy-related greenhouse gas emissions—Evidence from the G7 - Chen, Yuze; Chen, Ying; Zhang, Liuyue; Li, Zhi (Frontiers in Energy Research, 2023)
The massive consumption of energy promotes rapid economic growth, but it also unavoidably results in a large amount of greenhouse gas emissions, which seriously hinders society’s green and low-carbon development. This paper aims to explore the real impact of renewable energy and digitalization on greenhouse gas emissions from an energy-related perspective using advanced panel econometrics methods based on G7 panel data for 1990–2020. Economic growth and energy efficiency are also considered as control variables. Due to the nonlinear properties of panel data, the moment quantile regression approach is utilized in this research. The findings show that slope heterogeneity is widespread, section-dependent, and has a long-term equilibrium relationship. In addition, digitalization, renewable energy, and energy efficiency can reduce energy-related greenhouse gas emissions and ease environmental pressures. Economic expansion, on the other hand, remains an important positive driver for energy-related greenhouse gas emissions. The results of this study are robust and the causal relationships between variables are tested. Based on the conclusion presented above, this study advises the G7 economies to expand investments in renewable energy and digitalization to promote energy system transformation and pave the road for global decarbonization objectives to be met.